Populus luzae (Salicaceae), a new species of white poplar endemic to the western Transmexican Volcanic Belt, in Zapopan, Jalisco, Mexico - Vázquez-García, J. Antonio; Muñiz-Castro, Miguel Ángel; Padilla-Lepe, Jesús; Pulido Ávila, María Guadalupe; Nieves Hernández, Gregorio; Martínez González, Rosa Elena (Phytotaxa, 2017)
Populus luzae, a new species of white poplar from the western Transmexican Volcanic Belt, Zapopan, Jalisco, Mexico, is described and illustrated. Populus luzae belongs to section Populus and is morphologically close to P. guzmanantlensis, but it differs from the latter in having smaller size and soboliferous habit, narrower twigs and petioles, ovate to ovate-deltoid and chartaceous leaf blades, adaxial leaf surface with less depressed veins, abaxial surface puberulent, thrice smaller ovate male bracteoles with entire margin, twice longer female bracteoles sparsely denticulate but none lobed, smaller number of pistillate flowers, capsules pubescent, twice longer mature male inflorescence, and a lax and longer infrutescence.